Biochemistry and hematology parameters of the San Cristóbal Galápagos tortoise (Chelonoidis chathamensis). Issue 1 (16th February 2018) - Lewbart, Gregory A; Griffioen, John A; Savo, Alison; Muñoz-Pérez, Juan Pablo; Ortega, Carlos; Loyola, Andrea; Roberts, Sarah; Schaaf, George; Steinberg, David; Osegueda, Steven B; Levy, Michael G; Páez-Rosas, Diego
Abstract : The San Cristóbal Galapagos tortoise, Chelonoidis chathamensis, is native to San Cristóbal, the most eastern and oldest island of the Galapagos Archipelago. Although numerous studies on the ecology, behavior and genetics of Galapagos tortoises have been published, little is known about the health status of these animals. Here we report blood values from clinically healthy tortoises. Abstract: As part of a planned introduction of captive Galapagos tortoises ( Chelonoidis chathamensis ) to the San Cristóbal highland farms, our veterinary team performed thorough physical examinations and health assessments of 32 tortoises. Blood samples were collected for packed cell volume (PCV), total solids (TS), white blood cell count (WBC) differential, estimated WBC and a biochemistry panel including lactate. In some cases not all of the values were obtainable but most of the tortoises have full complements of results. Despite a small number of minor abnormalities this was a healthy group of mixed age and sex tortoises that had been maintained with appropriate husbandry. This work establishes part of a scientific and technical database to provide qualitative and quantitative information when establishing sustainable development strategies aimed at the conservation of Galapagos tortoises.